2020
DOI: 10.1155/2020/3034260
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Photoplethysmography System for Noninvasive Monitoring of Hemoglobin Concentration

Abstract: Background. Traditional invasive hemoglobin (Hb) detection led to delayed diagnosis, operational inefficiency, incorrect critical decision making, and uncomfortable patient experience. To facilitate real-time total hemoglobin (tHb) monitoring, a portable prototype of a noninvasive Hb detection system was developed, and the accuracy of Hb predicted based on partial least squares (PLS) as well as backpropagation artificial neural network (BP-ANN) models was validated. Results. The prototype was combined with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A non-invasive HGB concentration level prediction approach based on photoplethysmography (PPG) signals was presented. The system analyses PPG characteristics features utilizing a variety of machine learning methods [20]. Following the analysis of the datasets (PPG signals) obtained from 33 individuals who illuminated light with their fingers over the course of ten periods, 40 distinctive characteristics were identified.…”
Section: Related Workmentioning
confidence: 99%
“…A non-invasive HGB concentration level prediction approach based on photoplethysmography (PPG) signals was presented. The system analyses PPG characteristics features utilizing a variety of machine learning methods [20]. Following the analysis of the datasets (PPG signals) obtained from 33 individuals who illuminated light with their fingers over the course of ten periods, 40 distinctive characteristics were identified.…”
Section: Related Workmentioning
confidence: 99%
“…Kwon et al [ 12 ] developed a device for collecting PPG signals and utilized ensemble random forest (RF) and extreme gradient boosting to predict Hb concentration. In our previous study [ 13 ], we developed a portable non-invasive Hb detection system based on eight channel PPG signals. Partial least squares (PLS) and backpropagation artificial neural network (BP-ANN) algorithms were used to construct the Hb prediction model, and the result showed that the system has the potential for non-invasive Hb detection.…”
Section: Introductionmentioning
confidence: 99%